2020
DOI: 10.1007/s42832-020-0026-6
|View full text |Cite
|
Sign up to set email alerts
|

Soil fungal community is more sensitive to nitrogen deposition than increased rainfall in a mixed deciduous forest of China

Abstract: Nitrogen (N) deposition and intensified rainfall can strongly affect soil microbial community, but compared with available studies on bacteria, those on soil fungi are quite limited. Here we carried out a field experiment in a mixed deciduous forest of China to study the influences of increased N deposition and rainfall on soil fungi by using quantitative PCR and high-throughput sequencing method. The results demonstrated that (1) N addition significantly increased fungal abundance and alpha diversity (richnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 62 publications
4
13
4
Order By: Relevance
“…Additionally, consistent with our first hypothesis, we observed that N addition significantly increased the fungal α-diversity at the short-term site (>10%), but little enhanced at the long-term site (<2%; Figures 2A – C ), suggesting that soil fungal species could be sensitive to short-term N addition, and may adapt to long-term N enrichment in the tropical forest. Our results are in line with some of the observations from other forest ecosystems ( Entwistle et al, 2013 ; Zhao et al, 2020 ). For instance, Zhao et al (2020) revealed that 5 years of N addition increased the fungal α-diversity in a mixed deciduous forest; while Entwistle et al (2013) showed there were no significant effects on fungal α-diversity under more than 15 years of N addition.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Additionally, consistent with our first hypothesis, we observed that N addition significantly increased the fungal α-diversity at the short-term site (>10%), but little enhanced at the long-term site (<2%; Figures 2A – C ), suggesting that soil fungal species could be sensitive to short-term N addition, and may adapt to long-term N enrichment in the tropical forest. Our results are in line with some of the observations from other forest ecosystems ( Entwistle et al, 2013 ; Zhao et al, 2020 ). For instance, Zhao et al (2020) revealed that 5 years of N addition increased the fungal α-diversity in a mixed deciduous forest; while Entwistle et al (2013) showed there were no significant effects on fungal α-diversity under more than 15 years of N addition.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in line with some of the observations from other forest ecosystems ( Entwistle et al, 2013 ; Zhao et al, 2020 ). For instance, Zhao et al (2020) revealed that 5 years of N addition increased the fungal α-diversity in a mixed deciduous forest; while Entwistle et al (2013) showed there were no significant effects on fungal α-diversity under more than 15 years of N addition. Different response patterns between short- and long-term N additions in the present study could be attributed to the sensitivity of fungal species to N availability.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…2a-c), suggesting that soil fungal species could be sensitive to short-term N addition, and longterm N enrichment may result in the acclimatization of the soil fungal community in the tropical forest soil. Our results are in line with some of the observations from other forest ecosystems [50,51]. For instance, Zhao et al [50] revealed that 5 years of N addition increased the fungal α-diversity in a temperate forest, while Entwistle et al [51] showed there were no significant effects on fungal α-diversity under more than 15 years of N addition.…”
Section: Soil Fungal Diversity and Community Composition Were More Sesupporting
confidence: 92%
“…Our results are in line with some of the observations from other forest ecosystems [50,51]. For instance, Zhao et al [50] revealed that 5 years of N addition increased the fungal α-diversity in a temperate forest, while Entwistle et al [51] showed there were no significant effects on fungal α-diversity under more than 15 years of N addition. We speculated that the different response patterns between short-and long-term N addition in the present study could be attributed to the sensitivity of fungal species to N availability and the niche differentiation.…”
Section: Soil Fungal Diversity and Community Composition Were More Sesupporting
confidence: 92%